Genome-wide analysis emancipates genomic diversity and signature of selection in Altay white-headed cattle of Xinjiang, China - Chen, Jialei; Wang, Yushu; Qi, Xingshan; Cheng, Haijian; Chen, Ningbo; Ahmed, Zulfiqar; Chen, Qiuming; Lei, Chuzhao; Yang, Xueyi (Frontiers in Genetics, 2023)
Altay white-headed cattle have not received enough attention for several reasons. Due to irrational breeding and selection practices, the number of pure Altay white-headed cattle has decreased significantly and the breed is now on the eve of extinction. The genomic characterization will be a crucial step towards understanding the genetic basis of productivity and adaptability to survival under native Chinese agropastoral systems; nevertheless, no attempt has been made in Altay white-headed cattle. In the current study, we compared the genomes of 20 Altay white-headed cattle to the genomes of 144 individuals in representative breeds. Population genetic diversity revealed that the nucleotide diversity of Altay white-headed cattle was less than that of indicine breeds and comparable to that of Chinese taurus cattle. Using population structure analysis, we also found that Altay white-headed cattle carried the ancestry of the European and East Asian cattle lineage. In addition, we used three different methods (FST, θπ ratio and XP-EHH) to investigate the adaptability and white-headed phenotype of Altay white-headed cattle and compared it with Bohai black cattle. We found EPB41L5, SCG5 and KIT genes on the list of the top one percent genes, these genes might have an association with environmental adaptability and the white-headed phenotype for this breed. Our research reveals the distinctive genomic features of Altay white-headed cattle at the genome-wide level.